2018
DOI: 10.3389/fphys.2018.01557
|View full text |Cite
|
Sign up to set email alerts
|

Plasticity in the Sensitivity to Light in Aging: Decreased Non-visual Impact of Light on Cognitive Brain Activity in Older Individuals but No Impact of Lens Replacement

Abstract: Beyond its essential visual role, light, and particularly blue light, has numerous non-visual effects, including stimulating cognitive functions and alertness. Non-visual effects of light may decrease with aging and contribute to cognitive and sleepiness complaints in aging. However, both the brain and the eye profoundly change in aging. Whether the stimulating effects light on cognitive brain functions varies in aging and how ocular changes may be involved is not established. We compared the impact of blue an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
23
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 54 publications
0
23
1
Order By: Relevance
“…Recent functional magnetic resonance imaging data suggest a plasticity to light sensitivity in aging, such that after approximately 4 years of surgery, lens replacement did not significantly affect daytime light impact on cognitive brain function (associated with 0-back and 2-back task performance). 26 These results suggest that some aspects of cognitive brain function may adapt to the progressive decrease in daytime light exposure in aging. Importantly, sleep ailments are common in older patients with cataract, who subjectively report difficulties initiating and/or maintaining sleep, and impoverished subjective sleep quality, which can be alleviated after IOL replacement cataract.…”
Section: Discussionmentioning
confidence: 91%
“…Recent functional magnetic resonance imaging data suggest a plasticity to light sensitivity in aging, such that after approximately 4 years of surgery, lens replacement did not significantly affect daytime light impact on cognitive brain function (associated with 0-back and 2-back task performance). 26 These results suggest that some aspects of cognitive brain function may adapt to the progressive decrease in daytime light exposure in aging. Importantly, sleep ailments are common in older patients with cataract, who subjectively report difficulties initiating and/or maintaining sleep, and impoverished subjective sleep quality, which can be alleviated after IOL replacement cataract.…”
Section: Discussionmentioning
confidence: 91%
“…This may be important, if the associations between pupil measures and measures such as sleepiness are very short-lived and very sensitive to phasic variations, arising for instance from transient changes in motivation or effort [20]. In addition, our study only includes healthy young men aged 18 to 30 years when age and sex have been suggested to influence light sensitivity [61,62]. One should bear in mind that the associations between pupil measures and subjective sleepiness and objective alertness may just be weak, at least compared to other parameters such as PVT performance and not easy to put forward even with a sample of 20 individuals.…”
Section: Discussionmentioning
confidence: 99%
“…Past research has suggested the light-evoked modulation of several prefrontal regions. For example, blue (as opposed to green or orange) light exposure concurrent with an auditory working memory task has been shown to increase activity in the left middle frontal gyrus 12,13 and decrease ACC activity 13 . Furthermore, blue (as opposed to amber) light has been reported to decrease ACC activation following an emotional anticipation task 63 .…”
Section: Discussionmentioning
confidence: 99%